P0973ALLOSTERIC C-C CHEMOKINE RECEPTOR TYPE 2 (CCR2) INHIBITION IMPROVES RENAL FUNCTION IN A MURINE MODEL OF DIABETIC NEPHROPATHY. (6th June 2020) - Miao, Zhenhua; Ertl, Linda S; Zhao, Bin; Wang, Yu; Newland, Dale; Zeng, Yibin; McMahon, Jeffrey; Liu, Xiaoli; Dang, Ton; Miao, Shichang; Zhang, Penglie; Li, Chris; et al.
Abstract: Background and Aims: Diabetic nephropathy (DN) is a syndrome characterized by pathological levels of proteinuria, glomerular lesions and reduction in the glomerular filtration rate (GFR) in diabetic patients. Several lines of evidence support a role of CCR2 in the pathogenesis of DN. Recent studies have demonstrated that existing small molecule CCR2 antagonists can be placed in two classes, distinguished by their interaction with one of two distinct binding sites on CCR2: an extracellular site for which antagonists compete directly with native ligands (the orthosteric site), or an intracellular allosteric binding site. To better understand the functional differences between these antagonists we compared an example of each class in a murine model of DN. Our results revealed that the allosteric, but not the orthosteric CCR2 inhibitors ameliorated the proteinuria and improved glomerular histopathology in this model of DN. Method: We used db/db mice to model DN. Several structurally distinct CCR2 inhibitors with that bind to either the allosteric (CCR2-RA-[R] and CCX872) or orthosteric (MK-0812 and CCX598) sites were compared. Pharmacokinetic (PK) properties and renal functional parameters were assessed, including trough drug levels and proteinuria (urinary albumin excretion rate UAER; urine albumin creatinine ratio UACR). Histopathology and electron microscopy (EM) were performed to assess any potential tissue-protective effects of the antagonists. Results: Both the allosteric inhibitors (CCR2-RA-[R] and CCX872) and the orthosteric inhibitors (MK-0812 and CCX598) were potent CCR2 antagonists with desirable PK in mouse in so far as both classes effectively blocked CCR2-mediated monocyte migration into the peritoneal cavity in the thioglycollate-induced peritonitis model. At comparable drug coverage levels, CCR2-RA-[R] and CCX872 rapidly and significantly reduced UAER/UACR (CCX872: 70 % at day 7 vs vehicle, p<0.0001; and 60 % at day 14 vs vehicle, p=0.001; CCR2-RA-[R]: 60 % at day 7 vs vehicle, p=0.0001; and 58 % at day 14 vs vehicle, p=0.005), but MK-0812 and CCX598 did not exhibit proteinuria lowering effect. Histological parameters including glomerular injury and glomerular basement membrane (GBM) thickness were also improved after CCX872 treatment in db/db mice. Conclusion: Allosteric antagonists of CCR2 provide significant and rapid renal protection in the db/db murine model of DN, as evidenced by improvements in renal function and histological parameters, while potent orthosteric CCR2 antagonists were not effective in the model. Our data suggest that targeting the effectiveness of CCR2 antagonists in DN are directly dependent on binding to the allosteric site of CCR2.